1996
DOI: 10.1055/s-2007-972871
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strength Training on Blood Pressure Measured in Various Conditions in Sedentary Men

Abstract: To examine the effect of long term strength training on heart rate and blood pressure, measured in different conditions, and on their variability, thirty healthy, previously sedentary men were randomized into a training and a control group. The strength training program consisted of 48 training sessions on a multigym apparatus at a frequency of 3 sessions each week, involving leg press, bench press, leg curl, shoulder press, leg extension and sit ups. The control group was asked not to change their sedentary l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 6 publications
3
38
0
6
Order By: Relevance
“…Hagberg et al 27 also demonstrated a decrease in SBP (20 mm Hg) in hypertensive men following 9 months of low-to moderate-intensity aerobic training, with a concomitant decrease in DBP (11-12 mm Hg). One previous study 28 reported that 4 months of endurance training in middle-aged men resulted in no changes in resting SBP and o5 mm Hg decrease in resting DBP. Our results support these earlier studies, 27,28 indicating that exercise training has beneficial effects in individuals with pre-to stage-1 hypertension (mean BP 139/79 mm Hg) with as little as 4 weeks of moderate-intensity exercise.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Hagberg et al 27 also demonstrated a decrease in SBP (20 mm Hg) in hypertensive men following 9 months of low-to moderate-intensity aerobic training, with a concomitant decrease in DBP (11-12 mm Hg). One previous study 28 reported that 4 months of endurance training in middle-aged men resulted in no changes in resting SBP and o5 mm Hg decrease in resting DBP. Our results support these earlier studies, 27,28 indicating that exercise training has beneficial effects in individuals with pre-to stage-1 hypertension (mean BP 139/79 mm Hg) with as little as 4 weeks of moderate-intensity exercise.…”
Section: Discussionmentioning
confidence: 92%
“…One previous study 28 reported that 4 months of endurance training in middle-aged men resulted in no changes in resting SBP and o5 mm Hg decrease in resting DBP. Our results support these earlier studies, 27,28 indicating that exercise training has beneficial effects in individuals with pre-to stage-1 hypertension (mean BP 139/79 mm Hg) with as little as 4 weeks of moderate-intensity exercise. Our 3-4 mm Hg decreases in DBP and SBP parallel those recently reported in a meta-analysis by Fagard,29 who has shown that AE decreases in BP in normotensives of À3.0 (SBP) mm Hg and À2.4 (DBP) mm Hg with even greater reductions in resting BP in hypertensives (À6.9 and À4.9 mm Hg in SBP and DBP, respectively).…”
Section: Discussionmentioning
confidence: 92%
“…Foram encontradas 12 referências sobre o treinamento com pesos em longo prazo e a PA de repouso em normotensos (7,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) e seis referências em hipertensos (5,32,(40)(41)(42)(43) . Dos estudos com normotensos, duas referências possuíam dois grupos experimentais (35,37) .…”
Section: Treinamento Com Pesos E Pressão Arterial De Repousounclassified
“…Dessa forma, envolvendo normotensos, foram considerados 14 grupos de treinamento. Desses grupos envolvendo normotensos, 11 reportaram aumento significativo da força muscular (7,29,30,32,(34)(35)(36)(37)39) ; cinco, redução na PAS (7,31,35,37) ; quatro, redução na PAD (7,31,35) . Os quatro que reportaram redução na PAD também relataram redução na PAS.…”
Section: Treinamento Com Pesos E Pressão Arterial De Repousounclassified
See 1 more Smart Citation